2022
DOI: 10.1155/2022/4289905
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Low-Dose Esketamine for Reduction of Propofol Injection Pain: A Randomized Controlled Trial

Abstract: Background. Propofol-induced injection pain is a common adverse effect during the induction of general anesthesia. The purpose of this study is to investigate the effect of low-dose esketamine in preventing propofol injection pain. Methods. In this double-blind, randomized, controlled trial, patients scheduled for elective ear surgery under general anesthesia received either normal saline (NS), or 40 mg lidocaine, or 0.15 mg/kg esketamine 30 seconds before manual injection of propofol. The primary outcome of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In our study, the propofol–esketamine mixture (ESK-20 group) was effective in preventing PIP (decreased from 63.3% to 33.3%), and no patient reported severe pain. Pretreatment with esketamine (0.15–0.25 mg/kg) before injection of propofol significantly reduced the incidence of PIP ( Li et al, 2022a ; Fu et al, 2022 ). The mechanism by which esketamine reduces PIP may be related to its action on the peripheral NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the propofol–esketamine mixture (ESK-20 group) was effective in preventing PIP (decreased from 63.3% to 33.3%), and no patient reported severe pain. Pretreatment with esketamine (0.15–0.25 mg/kg) before injection of propofol significantly reduced the incidence of PIP ( Li et al, 2022a ; Fu et al, 2022 ). The mechanism by which esketamine reduces PIP may be related to its action on the peripheral NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org (0.15-0.25 mg/kg) before injection of propofol significantly reduced the incidence of PIP (Li et al, 2022a;Fu et al, 2022). The mechanism by which esketamine reduces PIP may be related to its action on the peripheral NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, propofol is a cardiovascular depressant and can lead to adverse reactions such as hypotension and bradycardia; these reactions may be attributed to a decrease in cardiac output, peripheral vascular resistance, or both, as well as an increase in venous capacitance or a decrease in sympathetic nervous system basal activity [9] . Meanwhile, the injection pain of propofol is a common adverse reaction [31] . According to previous reports, the incidence of injection pain caused by propofol can reach 28-90% and averages approximately 60-70% [32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…[6] To mitigate this risk, a pharmacological remedy such as esketamine, which is an antagonist of the N-methyl-D-aspartate receptor, is sometimes used in low doses before induction to avoid propofol injection pain and is known to increase blood pressure as a side effect. [14,15] Previous studies observed that this effect of esketamine can be used to improve hemodynamic stability in patients undergoing procedures under general anesthesia. [15][16][17][18][19][20][21][22] In light of the evidence from previous studies, we hypothesize that esketamine may improve blood pressure during the induction phase of the procedure since it stimulates the sympathetic nervous system, making it an ideal drug for the induction of anesthesia in unstable patients.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Previous studies observed that this effect of esketamine can be used to improve hemodynamic stability in patients undergoing procedures under general anesthesia. [15][16][17][18][19][20][21][22] In light of the evidence from previous studies, we hypothesize that esketamine may improve blood pressure during the induction phase of the procedure since it stimulates the sympathetic nervous system, making it an ideal drug for the induction of anesthesia in unstable patients. [23,24]…”
Section: Introductionmentioning
confidence: 99%